Performance Measures of Data Network Node with Buffer Threshold Control - Rindzevičius, R.; Adlys, G. (Elektronika ir Elektrotechnika, 2007)
We propose analysis of the data network node, which is using for transmission unreliable channel with constant bit transmission rate. For queuing system with finite buffer capacity and data packet losses the inter arrival time of high and low priority data packets flow and the transmission times of each priority data packet are exponentially distributed. The system buffer threshold control mechanism in data network node is applied. Research is in progress to develop analytical models for such network data packets transmission node which is using reliable channel without failures in one case and unreliable channel in other case. Using our proposed analytical models we can easily evaluate system performance measures such as data packet losses, mean value of waiting time in buffer, mean number of data packets in queue, mean number of data packets in the system. The results from analytical model of some performance measures are taken in figures. The processes in an unreliable channel data network queuing node are based on the Markov chains. The proposed analytical system models are suitable for analysis network node with finite data packets buffer. When the system buffer capacity is high analytical model for such queuing system node becomes very complicated. Simulation methods are applied for analysis the systems with infinite buffer. lll. 11, bibl. 8 (in English; summaries in English, Russian and Lithuanian).